How to struggle with exclusionary right-wing populism: evidence from Turkey. Issue 1 (2nd January 2023) - Erçetin, Tuğçe; Boyraz, Cemil
ABSTRACT: This paper investigates the new character of the strategy of the Republican People's Party (CHP) using populism to combat the success of the ruling Justice and Development Party (AKP). We consider populism along a left-right axis in terms of the differentiation of exclusionary and inclusionary approaches and conduct a content analysis of campaign speeches by Ekrem İmamoğlu during the 2019 local elections, as well as speeches of the party elites given during the currency crisis of 2018 and the COVID-19 pandemic. We argue that an alternative to the exclusionary right-wing populism may construct images of egalitarianism, participatory budgeting, and agrarian populism instead of mobilizing security or survival issues.